The Influence of Pop-Up Book Media on the Speaking Skills of Grade III MI Students - Puja Fauziah; Idah Faridah Laily; Syibli Maufur (UIN Siber Syekh Nurjati Cirebon, 2024)
This Study aims to determine the effect of pop-up book media on the speaking skills of class III MI student. This study used a quantitative approach, with a pre-eksperimental method and a research design using a one group pretest posttest design. The population in this study were all student of class III B and sample of this study consisted of 27 students, while the sampling used a saturated sample. Data collection techniques using observation and test observations are used to find out how learning uses pop-up book media while test are used to obtain speaking skills data using performance test where students are asked to tell stories data analysis techniques use normality test, homogeneity test, paired sample hypothesis testing test. The results of the application of pop-up book media using observation obtained a value of 96%, meaning that the teacher had used learning media according to the learning stages. and from the results of the posttest obtained an average value of 71.11. homogeneity obtained a sig value of 0.374>0.05, it was concluded that the variance of the data was homogeneous. From the results of the paired sample test, the sig value was obtained. 0.000<0.05 then H0 is rejected and Ha is accepted, meaning that the pop-up book media has a significant effect on the speaking skills of class III MI students. So the implication of this research is that pop-up book media can effect the speaking skills of class III MI studentsKeywords: Speaking Skills, Pop-Up Book Media, Indonesian Language Lerning